Social Anxiety in Students with Specific Learning Disorders Based on Emotion Regulation and Emotional Intelligence: The Mediating Role of Perceived Self-Efficacy. - Rostami, Parisa; Eyni, Sanaz; Zemestani, Mehdi (Journal of Comprehensive Pediatrics, 2024)
Background: One of the basic challenges faced by children with specific learning disorders (SLD) is social-emotional problems. Objectives: Considering the importance of social anxiety in interacting with others and its negative consequences in the family, society, and academic life of students with specific learning disabilities, the present study aims to develop a causal model of social anxiety in these students based on emotion regulation and emotional intelligence, taking into account the mediating role of perceived self-efficacy. Methods: The research employed a descriptive approach and utilized path analysis. The statistical population of this research comprised all the students with SLD who were referred to the student counseling centers and LD centers affiliated with the education organization of Sanandaj city in the academic year 2022 - 2023. The research sample consisted of 360 students aged between 8 and 12 years old with SLD, selected from the statistical population through purposeful sampling. In this research, the self-report version of Leibovitz's Social Anxiety Scale for children and adolescents by Masia-Warner et al., Shields and Cicchetti's emotion regulation inventory, Trait Emotional Intelligence Questionnaire by Mavroveli et al., and Muris' Children's Self-Efficacy Questionnaire were utilized. The fit indices of the model were also confirmed. Results: The variables of emotion regulation, perceived self-efficacy, and emotional intelligence directly affected the social anxiety of students with SLD. Additionally, the social anxiety of students with SLD was significantly related to the mediation of perceived self-efficacy with emotion regulation and emotional intelligence (P < 0.01). Conclusions: Therefore, to reduce the social anxiety of students with SLD, it is recommended that educators and experts develop educational programs to increase adaptive emotion regulation strategies, enhance perceived self-efficacy, and strengthen emotional intelligence.